2017
DOI: 10.1371/journal.pone.0170002
|View full text |Cite
|
Sign up to set email alerts
|

Knee Cartilage Thickness, T1ρ and T2 Relaxation Time Are Related to Articular Cartilage Loading in Healthy Adults

Abstract: Cartilage is responsive to the loading imposed during cyclic routine activities. However, the local relation between cartilage in terms of thickness distribution and biochemical composition and the local contact pressure during walking has not been established. The objective of this study was to evaluate the relation between cartilage thickness, proteoglycan and collagen concentration in the knee joint and knee loading in terms of contact forces and pressure during walking. 3D gait analysis and MRI (3D-FSE, T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 51 publications
9
50
0
2
Order By: Relevance
“…In porcine cartilage, Hamada et al found significant strain-related decreases in T1r 16 . These observations were confirmed by recent in vivo studies 23,24 .…”
Section: Introductionsupporting
confidence: 85%
“…In porcine cartilage, Hamada et al found significant strain-related decreases in T1r 16 . These observations were confirmed by recent in vivo studies 23,24 .…”
Section: Introductionsupporting
confidence: 85%
“…The VOI was defined as the volume of cartilage with either T 2 or T 1ρ relaxation times above 60 ms. This value is above the literature reported value of 50 ms for healthy cartilage (Bolbos et al, 2008;Li et al, 2011;Stahl et al, 2009;Surowiec et al, 2014;Van Rossom et al, 2017). Similarly, if no relaxation time exceeded this limit, the VOI was defined as "0".…”
Section: Tablementioning
confidence: 68%
“…We captured the trajectories of 68 reflective markers using thirteen infrared cameras (Vicon, Oxford, UK) recording at 100 Hz. We used a full body plug in gait marker set extended with 4 upper limb clusters, 4 lower limb clusters and one pelvis cluster (Van Rossom et al, 2017). We collected ground reaction forces using two force plates built in the treadmill at 1000 Hz.…”
Section: Methodsmentioning
confidence: 99%